(untitled) (Journal of Politics and International Studies, 2021)
This article is based on the argument that the Indian forces are using rape as a weapon against women in the disputed territory of Kashmir to eliminate the freedom struggle of Muslim population. According to different surveys and reports, more than 11 thousand women have been gang-raped and molested in occupied Kashmir by the Indian forces. The security forces are continuously exercising this weapon of sexual warfare on women as a punishment. The triggering force behind this tactic of sexual abuse is the ideology of Hindutva. Under this ideology, current Indian regime is trying to change the secular status of India into a Hindu State. The Modi government is supporting communal violence on minorities for its political purposes. So, the minority community in India in general and the Muslims in disputed territory of Kashmir in specific are facing state oppression at large. Minorities like the Muslims and the Christians are being termed as “threatening and hostile other” in India. This study investigates how India is securitizing the Kashmir conflict by enforcing sexual assaults against women through its security forces? Secondly, it also tries to find that answer of why the use of rape and sexual abuse are justified as a potent weapon by Indian forces in occupied Kashmir? A large number of security forces have been deployed in Kashmir to suppress the Kashmiri freedom struggle. The security forces are exercising mass rape as a weapon in Kashmir to curb their right to self-realization. Such growing sexual practices have adverse impacts on the physical and mental health of women. In the end, we conclude that such inhumane policies not only undermine the social fiber of the Kashmiri community but also it will disrupt the peace of the whole of Southeast Asia.